Estrategias metodológicas constructivistas para el fortalecimiento del proceso enseñanza-aprendizaje de Ciencias Naturales de 8vo año de Educación General Básica. Periodo 2022-2023. - Celi Santos, Erika Maricruz (2023)
The application of constructivist methodological strategies allowed students build their own knowledge, through the application of an intervention proposal, it helped to improve their academic performance, and therefore to strengthen the teaching and learning process, reason for which the present investigation was carried out, in order to strengthen the teaching and learning process of the students of eight year of basic education of the educative unit “Adolfo Valarezo” in Natural Science subject. Seeking to reach the proposal, qualitative research was used, that allowed to determine relevant characteristics of the educative environment, regarding the application of constructivist methodological strategies to improve the academic performance of students. The research approach corresponds to a participative action research, resulting in the significative improvement of the educative process. Thanks to the work made both students and teachers, that made it possible to strengthen the mentioned process and improve their academic performance, thanks to the management of constructivist methodologic strategies, with the respective techniques and resources. Likewise, the research design for its temporality is of transversal way. On the other hand, to have evidence of its validation, attitude and satisfaction measure scales were used. The achieved results reveal a considerable improvement regarding the academic performance and thus the strengthen of the classroom process, as a result of the application of the intervention proposal. Keywords: teaching-learning, academic performance, Constructivist pedagogical model, organization of information.